The effects of gender, age and region on rural teachers’ professional honor: an empirical analysis of survey data from seven provinces in China - Chen, Yuyi; Zhang, Wenhai; Sandoval-Hernandez, Andres (Frontiers in Education, 2025)
Professional honor is a critical factor shaping the recruitment and retention of teachers in rural China. This study examines the influence of demographic factors—gender, age, and region—on professional honor among 1,320 rural teachers across seven Chinese provinces. Using confirmatory factor analysis (CFA), the reliability of the professional honor scale was established (χ2/df = 6.249; RMSEA = 0.063). Comparative analyses revealed significant differences: female teachers reported higher levels of professional honor than their male counterparts; teachers in the Eastern Region exhibited greater professional honor than those in the Western Region; and teachers aged 31–40 displayed the lowest professional honor among all age groups. A multiple regression analysis identified gender, age, and region as significant predictors of professional honor, with gender moderating the relationship between public professional honor (PuPH) and personal professional honor (PePH). These findings have significant implications for addressing challenges in rural teacher prestige, including workforce feminization, age-related dynamics, and teacher migration from Western to Eastern regions. Recommendations are proposed to mitigate these challenges and enhance teacher retention in rural schools.